PENGARUH GANGGUAN PRIBADI, GANGGUAN EKSTERNAL, GANGGUAN ORGANISASI, KOMPETENSI, DAN KECAKAPAN PROFESIONAL TERHADAP KOMITMEN INDEPENDENSI AUDITOR (Studi Empiris pada Kantor Akuntan Publik di Batam dan Pekanbaru) - Shendi Yunita Rizky; Raja Adri Satriawan surya; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aims to invetigate the effect of Personal Disturbance, External Disturbance, Organizational Disturbance, Competency, and Professional Skills on the Auditors’ Independence in Public Accounting Firm (KAP) of Batam and Pekanbaru. This study is population. While responden is consisted by the fifty Public Accounting Firm (KAP) officers in Batam and Pekanbaru. The data was collected by distributing quetionnaires which isgiven to 60respondents, but only 50 (83%) respondents who fill out the questionnairescompletely and can be processed. The analysis tool used is multiple regression using SPSS program version 21. Based on t test results partially be known that the results of t test for variables personal disturbance, Organizational Disturbance, Competency, and Professional Skills was significantly on auditor independence wich thitung>ttabel. While the external disturbance dont have significantly effect on auditors independency.Keywords: Personal Disturbance, External Disturbance, Organizational Disturbance, Competency, Professional Skills and Auditors’ Independence